Tourists' Preferences in the Context of Their Psychological Well-Being: Conjoint Analysis - MŁYNKOWIAK-STAWARZ, Anna; BĘBEN, Robert (Journal of Environmental Management and Tourism, 2024)
The Purpose: The aim of the study is to determine how tourists' psychological well-being influences their preferences regarding various aspects of travel, such as the type of chosen destination, forms of leisure activities, and the expected intensity of social interactions. Design/methodology/approach: A conjoint analysis was conducted with a sample of 600 respondents. Participants completed a psychological well-being questionnaire and a conjoint analysis survey to assess their preferences for various aspects of travel. The sample was representative of the adult Polish population according to demographic data. Findings: The study found that the level of tourists' psychological well-being influences their preferences, particularly concerning the type of chosen tourist destination. Preferences for natural destinations were positively correlated with higher levels of psychological well-being. Originality: This research fills a gap in the literature by incorporating psychological well-being into the study of tourists' preferences, providing insights into how mental health can influence travel decisions. The findings underscore the importance of considering psychological factors in tourism management and marketing. Practical implications: Understanding the relationship between psychological well-being and travel preferences can aid in developing tourism offerings that support mental health, thereby contributing to overall social well-being. The study highlights the necessity of considering tourists' psychological well-being during the development of tourism offerings, as tourists' preferences are linked to their psychological well-being.